2019
DOI: 10.1101/777151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gonadotropes in medaka grow long extensions with varicosity-like swellings, projecting towards each other and blood vessels

Abstract: ___________________________________________________________________________Abbreviations: ACTH, Adrenocorticotropic hormone (mammals); DiI, lipophilic carbocyanine dye; FSH/Fsh, Follocle-stimulating hormone protein (mammals/fish); GFP, green fluorescent protein; GnRH/Gnrh, Gonadotropin releasing hormone protein (mammals/fish); IQR, interquartile range; LH/Lh, Luteinizing hormone protein (mammals/fish); Lhβ/Lhβ, Luteinizing hormone β subunit protein (mammals/fish); Lhb/lhb, Luteinizing hormone β subunit gene (m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…We found that Lh and Fsh cells are similar in morphology. They have similar volume in juveniles and in adults and show, both in vivo and in vitro, extensions allowing networking as previously shown for Lh (Grønlien et al 2019). Here, we show that Lh and Fsh cells show similar behaviour as they connect and cluster in cell culture using these extensions.…”
Section: Journal Of Endocrinologysupporting
confidence: 84%
See 1 more Smart Citation
“…We found that Lh and Fsh cells are similar in morphology. They have similar volume in juveniles and in adults and show, both in vivo and in vitro, extensions allowing networking as previously shown for Lh (Grønlien et al 2019). Here, we show that Lh and Fsh cells show similar behaviour as they connect and cluster in cell culture using these extensions.…”
Section: Journal Of Endocrinologysupporting
confidence: 84%
“…In medaka, Lh cells have been found to participate in the plasticity of the pituitary during puberty through hypertrophy and estrogen-sensitive hyperplasia during puberty (Fontaine et al 2019). Lh cells have also been shown to make neuron-like projections allowing homotypic networks (Grønlien et al 2019), to express gnrh receptors (gnrhr), and to respond to gnrh stimuli by increasing their action potential frequency and intracellular calcium concentration (Strandabo et al 2013. However, very little is known about Fsh cells and if and how they contribute to pituitary plasticity during puberty.…”
Section: Introductionmentioning
confidence: 99%
“…Long extensions have been described in fish gonadotropes both in situ and in culture ( 32 , 95 , 102 , 103 ). It is difficult to postulate as to the function of these processes but two plausible options are that these appendages are used for cell-cell communication or as a bridge between the cells and the vasculature.…”
Section: Functional Pituitary Network In Vertebratesmentioning
confidence: 99%
“…It is difficult to postulate as to the function of these processes but two plausible options are that these appendages are used for cell-cell communication or as a bridge between the cells and the vasculature. One line of evidence from cultured medaka cells ( 102 ) suggests that these processes do not relay signals between cells but are instead used for cell motility which serve to bring the cells together thus promoting cell-cell contacts and the formation of a network. It is hard to evaluate whether the processes serve the same role in vivo as in the adult medaka pituitary the cells are highly clustered yet the projections are still observed ( 102 ).…”
Section: Functional Pituitary Network In Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation